Vector competence evaluation of mosquitoes for Tahyna virus PJ01 strain, a new Orthobunyavirus in China - Cai, Tong; Liu, Ran; Jiang, Yuting; Jia, Nan; Jian, Xianyi; Cheng, Xiaolan; Song, Fenglin; Guo, Xiaoxia; Zhao, Tongyan (Frontiers in Microbiology, 2023)
Introduction Tahyna virus (TAHV), an arbovirus of the genus Orthobunyavirus, is a cause of human diseases and less studied worldwide. In this study, a new strain of TAHV was isolated from Aedes sp. mosquitoes collected in Panjin city, Liaoning province. However, the competent vector of TAHV in China is still unknown. Methods The genome of newly isolated TAHV was sequenced and phylogenetic analysis is performed. Aedes albopictus and Culex pipiens pallens were orally infected with artificial virus blood meals (1:1 of virus suspension and mouse blood), the virus was detected in the midgut, ovary, salivary gland and saliva of the mosquitoes. Then, the transmission and dissemination rates, vertical transmission and horizontal transmission of the virus by the mosquitoes were assessed. Results Phylogenetic analysis revealed that the virus shared high similarity with TAHV and was named the TAHV PJ01 strain. After oral infection with virus blood meals, Ae. albopictus showed positive for the virus in all tested tissues with an extrinsic incubation period of 2 days and a fluctuating increasement of transmission and dissemination rates. Whereas no virus was detected in the saliva of Cx. pipiens pallens. Suckling mice bitten by infectious Ae. albopictus developed obvious neurological symptoms, including inactivity, hind-leg paralysis and difficulty turning over, when the virus titer reached 1.70×105 PFU/mL in the brain. Moreover, TAHV was detected in the eggs, larvae and adults of F1 offspring of Ae. albopictus. Discussion Ae. albopictus is an efficient vector to transmit TAHV but Cx. pipiens pallens is not. Ae. albopictus is also a reservoir host that transmits the virus vertically, which further increases the risk of outbreaks. This study has important epidemiological implications for the surveillance of pathogenic viruses in China and guiding comprehensive vector control strategies to counteract potential outbreaks in future.